Students’ Perception Of Learning Efficiency and Creativity Towards Students Learning Achievement - Lussianda, Erfa Okta (Jurnal Curricula, 2018)
The purpose of this study is to determine the extent to which the students' perceptions of the efficiency of learning and creativity of learning to give effect to the student learning precedence STIE Persada Bunda. This research was conducted at the School of Economics Persada Bunda Pekanbaru. Techniques and data analysis is a descriptive analysis technique. Population amounted to 328 students STIE Persada Bunda with sample of 77 samples. To examine the instruments of this study using questionnaires to obtain analysis of validity, reliability, descriptive analysis, and use statistical analysis of multiple regression analysis as well as testing the hypothesis of T test and F test. The results of this study showed that the hypothesis proposed in this study had a significant effect between perceptions students about the efficiency of learning and learning creativity toward the achievement index. The value of T arithmetic for student perception variable about learning efficiency (X1) is 3,066 significant at level 0,059. Thus it can be seen that T arithmetic <t table is -3.066> 1.992 (sig 0.059 <0.05). For learning creativity variable (X2) The value of t table in α  = 0.05 is 1.992. t value is 5,044. so it can be seen that t count> t table, that is 5,044> 1,992. (sig 0.015 <0.05).